1971
DOI: 10.1149/1.2408209
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and Coulometric Studies of the Mechanism of Electrohydrodimerization of Diethyl Fumarate in Dimethylformamide Solutions

Abstract: The reduction of diethyl fumarate (DEF) in tetra‐n‐butylammonium iodide (TBAI)‐dimethylformamide (DMF) solutions at a platinum electrode has been studied by cyclic voltammetry, double potential step chronoamperometry, and controlled potential coulometry. The chronoamperometric response for several possible mechanisms of electrohydrodimerization has been obtained by digital simulation techniques, and a method for distinguishing among the mechanisms suggested. Results of double potential step chronoamperometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(68 citation statements)
references
References 0 publications
6
61
1
Order By: Relevance
“…A first series of extended studies on the mechanism of the electrohydrodimerization of activated olefins in nonaqueous solvents, mainly dimethylformamide (DMF) and acetonitrile concluded that it involves the radical-radical coupling of two anion radicals (rr mechanism in Scheme 1) rather than the reaction of one anion radical on the starting olefin which would lead to a secondary anion radical that is further reduced at the electrode or in the solution (rs mechanism in Scheme 1) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In all cases, small amounts of water were added to the solution to avoid the electron stoichiometry being less than one.…”
Section: The Radical-radical Coupling Mechanismmentioning
confidence: 99%
“…A first series of extended studies on the mechanism of the electrohydrodimerization of activated olefins in nonaqueous solvents, mainly dimethylformamide (DMF) and acetonitrile concluded that it involves the radical-radical coupling of two anion radicals (rr mechanism in Scheme 1) rather than the reaction of one anion radical on the starting olefin which would lead to a secondary anion radical that is further reduced at the electrode or in the solution (rs mechanism in Scheme 1) [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. In all cases, small amounts of water were added to the solution to avoid the electron stoichiometry being less than one.…”
Section: The Radical-radical Coupling Mechanismmentioning
confidence: 99%
“…b V vs. SRE; 0.050 V/sec. 1 This procedure is based on the fact that the boundary value problem comprising reactions [1]-151 is of the same form as that solved by Olmstead et al (13) when it is assumed that reaction [2] is fast and that the diffusion coefficients of the radical anion and ion pair are identical. The formulation treats the sum of the radical anion and ion pair concentrations as a new variable.…”
Section: Resultsmentioning
confidence: 99%
“…Childs et al (1) noted that the addition of sodium or lithium ions to the supporting electrolyte caused a substantial increase in the rate of dimerization of the radical anions of diethyl fumarate. Lithium also had the effect of decreasing the importance of polymerization side reactions as evidenced by an increase of the coulometric n-value to unity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…And studies of these reactions led to an appreciation of their role in dimerization and polymerization (12). These eventually led to work demonstrating electronically conducting polymers.…”
Section: Undoing a Prevailing Modelmentioning
confidence: 99%